Tuberkulózní koxitida - stupně postižení (soubor kazuistik) - Netval, Miroslav; Hudec, T; Hach, J (Acta chirurgiae orthopaedicae et traumatologiae Čechoslovaca, 2007)
Tuberculous hip arthritis ranks third in the classification of orthopedic tuberculosis, after tuberculosis of the spine and knee joint. It accounts for about 15 % of all orthopedic tuberculosis. The aim of this paper is to demonstrate the etiology, clinical presentation and forms of disease on the case reports of six patients. The scope of disease is wide - from a mild reversible synovial form, then fibrous or bone ankylosis, to severe destruction of the hip with subluxation or dislocation, pseudoarthrosis or chronic arthritis with a fistula. The wide diversity of clinical findings and difficulties is making diagnosis are often responsible for a late start of therapy. However, only an early and adequate treatment permits the prevention of irreversible damage to the hip joint or further complications.
Keywords: stupeň závažnosti nemoci; lidé; Tuberculosis, Osteoarticular; artritida; tuberkulóza osteoartikulární; Hip Joint; Arthritis; Humans; kyčelní kloub; Severity of Illness Index